Freegans in trouble. The axiological relationship between dirt and food - Pelska, Agata (Hybris, 2022)
This article is based on ethnographic research conducted among freegans in 2021. It explores issues of valuation linked to the cultural categories of food and dirt, which come together in a surprising way in the phenomenon of freeganism. The main questions addressed in the article are: why does the practice of freeganism arouse social controversy and even disgust? How do the participants of the movement deal with this confusion of axiologies - of dirt and food - that blatantly disrupts the cultural order? Using Mary Douglas'es structuralist theory of dirt (drawn primarily from her book Purity and Danger) and my field material, I also demonstrate the connections between freegan ethics, the phenomenon of wastefulness and the status of trash in culture, which freegans often consider to be arbitrarily and unjustifiably assigned.